Automated System for Irrigation and Fumigation Control in Physalis peruviana (Uvilla) Plantations - Yandún Velasteguí, Marco Antonio; Quiranza Arciniega, Anthony Alexander; Jiménez Jácome, Henrry Sebastián; Quilismal Tulcán, Jhon Jairo (Tierra Infinita, 2024)
This study focused on the development of an automated system for irrigation and fumigation control in Physalis peruviana (Uvilla) plantations. The main objective was to optimize irrigation and fumigation processes in plantations through the use of low-cost and easily accessible technology. Moisture, temperature, and proximity sensors were employed, controlled by an ESP32 microcontroller, and a mobile application was designed using Flutter to monitor and manage the system in real-time. The methodology included the implementation of an experimental approach with field tests, where the effectiveness of the automated system was evaluated. The results indicated a significant reduction in water consumption and an improvement in fumigation efficiency, contributing to an increase in uvilla crop productivity. The conclusions highlight the technical and economic feasibility of the proposed system, as well as its potential to be replicated in other agricultural contexts.
Keywords: Automated irrigation; fumigation; Physalis peruviana; agricultural technology